1969
DOI: 10.1111/j.1469-8749.1969.tb01461.x
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Infantile Autism

Abstract: SUMMARY The results are piesented of the first part of a study designed to clarify the diagnosis of infantile autism. The nine‐point scale devised by Creak and others in 1961 was used as the source of reference for data collection. The symptoms of a group of children clinically diagnosed as having infantile autism were analysed. Control groups of normal children, children diagnosed as rubella deaf, as cerebral palsied and as subnormal, were compared with the autistic test group. Using the method of numerical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Within the first screening phase, four instruments were used including the CABS (n = 15) [24], the ABC (n = 3)[60], the Checklist for Autism in Toddlers (CHAT) (n = 3) [13] and the Autism Spectrum Disorder in Adults Screening Questionnaire (ASDASQ) (n = 1) [61]. Three studies used the ABC and two used the CARS as screening tools after the first screening phase [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the first screening phase, four instruments were used including the CABS (n = 15) [24], the ABC (n = 3)[60], the Checklist for Autism in Toddlers (CHAT) (n = 3) [13] and the Autism Spectrum Disorder in Adults Screening Questionnaire (ASDASQ) (n = 1) [61]. Three studies used the ABC and two used the CARS as screening tools after the first screening phase [26].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reviewed the instruments used for case identification of ASC in mainland China [23]. It indicated that the Clancy Autism Behavior Scale (CABS) [24] and the Autism Behavior Checklist (ABC) [25] as screening instruments, and the Childhood Autism Rating Scale (CARS) [26] as a diagnostic instrument, were the most frequently used in mainland China. The CABS was developed in 1969 [24] and introduced into China in the late 1980s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, none of the ASD subjects fulfilled a DSM-IV diagnosis (American Psychiatric Association, 1996) of any mental disorders (schizophrenia, attention deficit/hyperactivity disorder, depressive disorder, and bipolar disorder), as well as suffered from epileptic seizures and fragile X syndrome on the basis of medical history reported by parents. TD controls were required to be free of psychiatric, neurological or physical disorders in the present or past on the basis of medical history reported by parents and with a score of <7 on the Clancy Autism Behavior Scale (CABS) (Clancy et al, 1969). To ensure the robustness of the experiments, none of the participants in any group were taking special drugs, such as psychotropic or immune-altering medications.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, none of the participants in any group were taking drugs. Exclusion criteria for both groups included medical history of epileptic seizures, head trauma, and known psychiatric, neurological or genetic disorders, and TD controls were with a score of < 7 on the Clancy Autism Behavior Scale (CABS) 57 .…”
Section: Methodsmentioning
confidence: 99%